(Re)source: the progression of humanity as companion to its landscape, through horticulture in Kathu - van der Walt, Zanré (My University, 2023)
Kathu is a mining town located in the Northern Cape province of South Africa. The town lies in the central region of the greater Kalahari. Apart from mining, Kathu, as a context, holds an interesting history and plays an important role in national and global heritage. By gaining a deeper understanding of this environment, we may discover that it holds a key to unlocking some profound mysteries relating to where we come from as an evolutionary species. We explore the nature of humanity’s relationship to its environment in ancient and modern times. And by magnifying the ways in which way may grow to reach higher states of consciousness and a greater awareness of our internal - and therefore external – landscapes, we may find that there is great value in cultivating intimate affection for the natural world. For it is in nature that we see the reflection of ourselves; the good, the bad, and the ugly. And this may very well point us in a direction whereby we can create a more salubrious and harmonious world for our own and our planet’s future. The proposed architectural intervention aims to provide a framework for sustainable human settlement development in a rural area, close to Sishen Iron Ore mine. It pursues the notion of De-urbanisation, and re-ruralisation through multiscale horticulture. Implementation of gravity fed open water channels will outline the spatial structure that underpins a community agriculture program. The roots of this project lie in the realm of township establishment, on a suburban scale. The concept of traditional property allotment is modified through design, as each property faces its road and waterway with an assigned greenhouse. The greenhouses serve as space for the production of local fresh produce, managed by the respective tenants. Whilst an educational and demonstrative precinct, set in the midst of a market street, form the microcosm of the scheme.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, 2023